2009 IEEE International Electric Machines and Drives Conference 2009
DOI: 10.1109/iemdc.2009.5075367
|View full text |Cite
|
Sign up to set email alerts
|

Operating charts for the Brushless Doubly-Fed Machine (BDFM)

Abstract: The Brushless Doubly-Fed Machine (BDFM) is an electrical machine that allows brushless operation in many applications where the Doubly-Fed Induction Generator (DFIG) is currently used. In recent years work on BDFM control means that the machine can now be run stably across its working range. However, little work has been done to define the working area in which BDFM can safely be operated without exceeding its material and stability limits. This paper sets out the theoretical backing for an operating chart of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…More insight in the brushless DFIM operating principles can be obtained using a brushless DFIM electric equivalent circuit (EEC). The brushless DFIM EEC is a tool to determine this machines steady-state operating characteristics [30][31][32][33]. A simple per phase EEC that has all windings referred to the power-winding is presented by Roberts et al [34] and shown in Fig.…”
Section: Brushless Dfim Operating Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…More insight in the brushless DFIM operating principles can be obtained using a brushless DFIM electric equivalent circuit (EEC). The brushless DFIM EEC is a tool to determine this machines steady-state operating characteristics [30][31][32][33]. A simple per phase EEC that has all windings referred to the power-winding is presented by Roberts et al [34] and shown in Fig.…”
Section: Brushless Dfim Operating Principlesmentioning
confidence: 99%
“…Standard EEC modelling techniques have been proven useful in determining basic operating characteristics [33,34], but magnetic saturation is often ignored. In addition, the extraction of EEC parameters from a brushless DFIM is not easy and obtaining a simple method to do so proves to be challenging.…”
Section: Brushless Dfim Modelling Techniquesmentioning
confidence: 99%
“…It is suggested in [5] that further limits should be placed on the electrical loading in each of the two windings to prevent either winding becoming excessively hot. The three electrnical loadings used are shown in table I.…”
Section: Bdfmmentioning
confidence: 99%
“…The structure of such a chart for the BDFM is presented in [5]. The chart must be calculated from equivalent circuit parameters.…”
Section: B Performancementioning
confidence: 99%